Mikro- i makrokontekst w procesie systemowej diagnozy psychopedagogicznej dzieci i młodzieży z trudnościami w uczeniu się - Krauze-Sikorska, Hanna (Wydawnictwo Naukowe UAM, 2014)
The process of diagnosing children and adolescents with learning difficulties is considered to be the initial and simultaneously the basic link of building a constructive process concentrated on prophylaxis and therapy to assist and support children’s development and activities. This article tries to determine the place diagnostic procedure should take up in the multi-faceted intervention system to help children and adolescents with learning difficulties. I present in it assumptions based on the systemic (or even systemic – constructivist) model, though I realize that such an approach does not facilitate the diagnosis because it requires opening up to dialogue with a “client” and the environments in which he or she operates, to view the problems of children and adolescents from different perspectives, including but not limited to the biographical perspective. The main aspect I focus on are the conditions to be fulfilled in order for the realization of the diagnostic process in systemic terms. The assumptions of the systemic approach in diagnosis are very inspiring both theoretically and practically, but their real inclusion into diagnostic practice raises dilemmas and doubts as we are faced with continuous challenges.
Micro- and Macro-context in the Process of Systemic Psycho-pedagogical Diagnosis of Children and Adolescents with Learning Difficulties
Keywords: determinants of learning disabilities; assumptions about systemic diagnosis; diagnostic value of systemic depiction; contexts in the process of systemic diagnosis